Description of mtDNA Markers of Loggerhead Marine Turtles from Caribbean Colombia (2012)
The loggerhead sea turtle (Caretta caretta) occurs throughout tropical, subtropical and temperate waters (Bolten & Witherington 2003). Once considered to be a nesting population of ~500 females, currently the loggerhead rookery along the Caribbean coast of Colombia is reported to be greatly reduced in size (Amorocho 2003). This population in Northern Colombia is considered to be part of the Northwestern Atlantic regional population (Conant et al. 2009), although detailed population structure data, based on molecular markers, are lacking from loggerheads that occur here. As a first step toward elucidating the relationship between loggerheads from Colombia and those from throughout the Wider Caribbean, we conducted preliminary assessments of mitochondrial DNA (mtDNA) haplotypes of nesting and foraging loggerhead turtles sampled in Colombia, using direct sequencing and phylogenetic inference. During 2008 and 2009, we collected blood samples from the dorsal cervical sinus from eight loggerhead turtles of the Colombian Caribbean: five nesting females from Don Diego beach (11°16’N, 73°45’W) and three juvenile turtles captured while they were foraging around San Martin de Pajarales Island (10°11’N, 75°47’W). Genomic DNA was extracted from each blood sample using a commercial kit (UltraClean™ Tissues & Cells, MO BIO Laboratories, Inc, California, USA).